Examining Alternative Forms of Utility Regulation: The Incentives and Disincentives of the Regulatory Structure - Gelder, Ralph; Dinan, Edward; Flanagan, David; Donahue, Joseph (Maine Policy Review, 1993)
The traditional form of regulating public utilities—command-and-control—has been found inadequate by some to cope with marketplace changes that have introduced competition into previously monopolistic markets. Alternative forms of regulation, particularly incentive regulation, have been developed in various areas of the nation in response to the new competitive utility environment. In these four short articles, former Maine Public Utilities Commission chair Ralph Gelder, New England Telephone Vice President for Maine, Edward Dinan, and Central Maine Power Company Vice President David Flanagan discuss these emergent utility issues. A fourth and quite different view of the present regulatory system and its alternatives is provided by Joseph Donahue, an Augusta attorney who frequently represents several major industries in utility proceedings.
Keywords: Maine; utility regulation; Maine Public Utilities Commission